Development of MPLS test-bed for network traffic engineering - Jusoh @ Tajudin, Mohd. Taufik (2005)
Providing Quality of Service (QoS) and Traffic Engineering (TE) capabilities in the Internet is essential, especially in supporting the requirement of real-time traffic, as well as mission critical applications. For that reason, the current Internet must be enhanced with new technology that enables it to offer capabilities for controlling its behaviour as needed. Multiprotocol Label Switching (MPLS) is an emerging technology that provides QoS and traffic engineering features in IP network. This study is mainly concerned on how to develop MPLS test-bed in order to assess MPLS functionalities. The goal is to develop MPLS test-bed using Linux operating system with kernel version 2.6.5 as the platform. In this work the MPLS test-bed consists of four MPLS routers and two host terminals. MPLS software package version 1.946 has been used to build up routers similar to existing routers in MPLS domain called as Label Switched Router (LSR). Once the routers are well configured, the connection between two routers is established to create Label Switched Path (LSP). This LSP connection is also used to create new LSP from ingress router to egress router. IP packets are sent from ingress router to host terminals to validate the test-bed. These packets were encapsulated with MPLS header and they are examined by using ‘tcpdump’ command in Linux terminal which shows that the test-bed is successfully developed. In order to enhance test-bed functionalities, packet generator can be added to the test-bed so that UDP and TCP throughput measurement can be done. Besides, RSVP and Diffserv can be integrated into the test-bed for future study.